Towards a Novel Model for Availability as a Service - Flauzino, José; Duarte Jr., Elias Procópio (Anais Estendidos do Latin-American Symposium on Dependable and Secure Computing (LADC); 2023: Anais Estendidos do XII Latin-American Symposium on Dependable Computing, 2023)
Highly Available systems often require sophisticated, expensive techniques. However, end-users may not have enough resources on their premises, or the knowledge to make their systems reach that goal. It may be fully impractical to expect an end-user to easily transform a regular application into a highly available one. In this work, we propose a novel perspective on Availability as a Service (AaaS). The proposed model has the potential to offer different levels of availability in a simplified fashion. AaaS has been often used to describe clouds that offer highly available services. Our proposal, on the other hand, is for the environment itself to provide, on demand, the functionality required for end-user systems to achieve specific levels of availability. We also envision that AaaS can go beyond the cloud. This includes the case in which AaaS is provided in a scenario we call Edge-Core-Cloud Continuum, where the network core plays a prominent role through NFV-COIN (Network Functions Virtualization - COmputing In the Network).